PENGARUH WORK-FAMILY CONFLICT TERHADAP TURNOVER INTENTION YANG DIMEDIASI OLEH KELELAHAN KERJA - Sanita Dhakirah; Nurul Hidayatinnisa; Riska Ayu Setiawati (Universitas Muhammadiyah Gresik, 2021)
Nowadays competitive business environment makes companies maximize employee performance with high working standards. It's become worse when the pressure's going to make the employee work role conflicts triggered only between work and family life (work-family conflict). This must be watched out for because it can cause , work exhaustion (and lead the desire to move (turnover intention). This research aimed to discuss whether there is an influence between work overload and work-family conflict on turnover intention and mediated by work exhaustion on the production of employees at PT. APM . Mechanical sampling for this research using proportionate stratified random sampling with a sample of 119 respondents. Statistical analysis method was used AMOS. The results indicated that work-family conflict has positif significant affect on work exhasution work-family conflict has positif significant affects on turnover intention.